Can children’s spelling of schwa vowels in stems be improved? - Rosa, João; Nunes, Terezinha (Educar em Revista, 2010)
Children in the early grades of primary school do not seem to have much awareness of morphemes. In this study, a priming paradigm was used to try to detect early signs of morphological representation of stems through a spelling task presented to Portuguese children (N= 396; age range 6 to 9 years). Primes shared the stem with the targets and contained well-articulated, stressed vowels; the stems of the target words contained non-stressed schwa vowels, which typically result in spelling difficulties. If priming proved effective, the well-articulated vowels in the prime should lead to improvement in the spelling of the schwa vowels in the targets. Primes were presented in two conditions: in only-oral or in oral-plus-written form. Effectiveness of priming was assessed by comparison with a no-priming condition. There was a significant interaction between priming effects and grade. No priming effects were detected in 6- and 7-year-old children; oral-plus-written priming produced higher rates of correct vowel spelling for 8- and 9-year-olds; only-oral priming was effective in improving the vowel spelling of 9-year-olds. Thus the older children used morphological information under priming conditions but there is no evidence to suggest that younger children did so.